PENGARUH MEDIA PEMBELAJARAN BERBASIS LESSONUP TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS XI SMAN 4 PALEMBANG - Nabilah Oktariani; Juaidah Agustina; Masnunah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using LessonUp-based learning media on students' short story writing skills. The background of this research is the low student engagement and performance in writing short stories due to the use of conventional methods that are less interactive. A quantitative approach with a quasi-experimental method was employed in this research. The design used was post-test only control group design, involving two groups: an experimental class using LessonUp and a control class using conventional methods. The population consisted of all eleventh-grade students at SMAN 4 Palembang, and samples were selected using cluster random sampling. Data collection was conducted using writing tests. The results showed that the experimental class obtained a higher average post-test score (87.46) compared to the control class (70.93). The data met the normality and homogeneity assumptions. The hypothesis test using an independent sample t-test indicated a significant difference between the two groups, with a Sig. (2-tailed) value of 0.000 and a t-count of 11.374, which is greater than the t-table value of 1.667. It can be concluded that the use of LessonUp-based media has a significant positive effect on students' short story writing skills.